A) - 3xy - (2x - y + 2xy) =
B) 4ab + (2a - 3ab) =
C) - (3p - r) _ 2r =
D) - st - ( -2t +s) =
E) 4 - (m + 5 - n) =
F)4g - (-2h + g - 3) =



Odpowiedź :

MertB

Cześć!

Szczegółowe wyjaśnienie:

a)

[tex] - 3xy - (2x - y + 2xy) \\ - 3xy - 2x + y - 2xy = \\ - 5xy - 2x + y[/tex]

b)

[tex]4ab + (2a - 3ab) = \\ 4ab + 2a - 3ab \\ ab + 2a[/tex]

c)

[tex] - (3p - r) - 2r = \\ - 3p + r - 2r \\ - 3p - r[/tex]

d)

[tex] - st - ( - 2t + s) \\ - st + 2t - s[/tex]

e)

[tex]4 - (m + 5 - n) \\ 4 - m - 5 + n \\ - 1 - m + n[/tex]

f)

[tex]4g - ( - 2h + g - 3) \\ 4g + 2h - g + 3 \\ 3g + 2h + 3[/tex]